Perancangan sistem informasi prodi Teknologi Rekayasa Perangkat Lunak (TRPL) - Ahmat Josi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The Software Engineering Technology Study Program (TRPL) of the Bangka Belitung State Manufacturing Polytechnic (Polmanbabel), is one of the study programs engaged in IT. Currently, the TRPL study program does not have a special information system for disseminating information, and archive media, making it difficult for the public to find information related to the TRPL study program. TRPL study program. One of the media that can help to disseminate information as well as study program archives is the information system media. Information system is an arrangement and collection consisting of hardware, software and implementation personnel who work in a sequential process and are jointly related to one another to produce a product. To build an information system can be done through several methods including the waterfall method, SLDC and web engineering. web engineering (web engineering) is a software engineering method used for the development of web-based systems or applications